Effects of an animated educational video on knowledge of cell-free DNA screening among Thai pregnant women: a randomized control trial - Nutta Nintao; Jittima Manonai; Rujira Wattanayingcharoenchai; Sommart Bumrungphuet; Wirada Hansahiranwadee; Wirada Dulyaphat; Werapath Somchit; Duangrurdee Wattanasirichaigoon; Maneerat Prakobpanich; Chayada Tangshewinsirikul (BMC Pregnancy and Childbirth, 2023)
Abstract Background In developing countries, pregnant women have insufficient knowledge about cell-free DNA screening. Reports from developed countries have found that various tools in prenatal genetic counseling can improve the knowledge of pregnant women who undergo cell-free DNA screening. Data are limited from developing countries where women have different baseline socio-educational backgrounds. The objective of this study was to compare the effects of an animated educational video combined with traditional counseling versus traditional counseling alone in changing pregnant women’s knowledge of cell-free DNA screening. Methods This study was a randomized control trial at an antenatal clinic. Eligible subjects who were Thai pregnant women, were randomized to either view or not view the 4-minute animated educational video explaining cell-free DNA screening. Both groups received traditional counseling. The women were asked to complete a Thai questionnaire assessing knowledge of the screening before and after intervention. The questionnaire consisted of three sections: demographic data of the research participants and their existing awareness about cell-free DNA testing; performance and limitations of cell-free DNA screening; and participants’ attitudes toward the positive screening. Primary outcome was the change in knowledge scores. Secondary outcomes were attitudes toward positive screening test, levels of satisfaction with counseling, and screening acceptance rates. Results Data from 83 women in the video group and 82 in the non-video group were analyzed. The knowledge score (range 0–18) change after counseling was significantly higher in the video group than the non-video group (+ 7.1 ± 3.3 vs + 4.2 ± 2.5; p = 0.03). There were no significant differences in attitudes toward positive screening test (p = 0.83), levels of satisfaction (p = 0.24), or screening acceptance rates (p = 0.15) between the groups. Conclusions Adding the video to traditional counseling was better than traditional counseling alone in improving pregnant women’s knowledge about cell-free DNA screening. Trial registration The study was retrospectively registered with the Thai Clinical Trials Registry (TCTR20210917001, 17/09/2021).